Super-resolution Microscopy – Applications in Plant Cell Research - Schubert, Veit (Frontiers in Plant Science, 2017)
Most of the present knowledge about cell organization and function is based on molecular and genetic methods as well as cytological investigations. While electron microscopy allows identifying cell substructures until a resolution of ~1nm, the resolution of fluorescence microscopy is restricted to ~200 nm due to the diffraction limit of light. However, the advantage of this technique is the possibility to identify and co-localize specifically labelled structures and molecules. The recently developed super-resolution microscopy techniques, such as Structured Illumination Microscopy (SIM), Photoactivated Localization Microscopy (PALM), Stochastic Optical Reconstruction Microscopy (STORM) and Stimulated Emission Depletion (STED) microscopy allow analysing structures and molecules beyond the diffraction limit of light. Recently, there is an increasing application of these techniques in cell biology. This review evaluates and summarizes especially the data achieved until now in analysing the organization and function of plant cells, chromosomes and interphase nuclei using super-resolution techniques.